Aloe barbadensis Based Bioactive Edible Film Improved Lipid Stability and Microbial Quality of the Cheese - Firdous Kouser; Sunil Kumar; Hina F. Bhat; Abdo Hassoun; Alaa El-Din A. Bekhit; Zuhaib F. Bhat (Foods, 2023)
An attempt was made to develop a bioactive edible film using carrageenan and A. vera gel for enhancing the storage quality of cheese using kalari, a popular Himalayan cheese, as a food-model system. The film was evaluated for various physicomechanical and oxidative properties (ABTS (2,2-azino-bis (3-ethylbenzothiazoline-6-sulfonate)) and DPPH (1,1-diphenyl-2-picrylhydrazyl) radical scavenging activities, total flavonoid and phenolic contents). Based on preliminary trials, 1% A. vera gel was found to be optimum. The addition of the gel resulted in a significant decrease in moisture content, transparency, solubility, and water-vapor transmission rate and increased the thickness and density of the film. The film showed antimicrobial properties against E. coli and significantly (p < 0.05) decreased the lipid-oxidation (thiobarbituric acid reactive substances, free-fatty acids, and peroxide values) and increased microbial-quality (total-plate, psychrophilic, and yeast/molds) of the samples during 4-week refrigerated storage (4 ± 1 °C). The film also exhibited a significant positive impact on the sensory quality of the cheese, indicating the potential for commercial applications for quality control of cheese during storage.